2017
DOI: 10.3389/fpsyg.2017.02285
|View full text |Cite
|
Sign up to set email alerts
|

Rapid L2 Word Learning through High Constraint Sentence Context: An Event-Related Potential Study

Abstract: Previous studies have found quantity of exposure, i.e., frequency of exposure (Horst et al., 1998; Webb, 2008; Pellicer-Sánchez and Schmitt, 2010), is important for second language (L2) contextual word learning. Besides this factor, context constraint and L2 proficiency level have also been found to affect contextual word learning (Pulido, 2003; Tekmen and Daloglu, 2006; Elgort et al., 2015; Ma et al., 2015). In the present study, we adopted the event-related potential (ERP) technique and chose high constraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Although all participants had Kannada as their first language (L1) and English as their second language (L2), the HSE participants in particular exhibited the use of more L2 vocabulary than L1, compared to the LSE counter-parts who predominantly used L1 over L2. This shift in the usage of L2 over L1 in the HSE group, could be attributed to the sequential change in the preferred language, possibly due to favorable contextual demands [40].…”
Section: Discussionmentioning
confidence: 93%
“…Although all participants had Kannada as their first language (L1) and English as their second language (L2), the HSE participants in particular exhibited the use of more L2 vocabulary than L1, compared to the LSE counter-parts who predominantly used L1 over L2. This shift in the usage of L2 over L1 in the HSE group, could be attributed to the sequential change in the preferred language, possibly due to favorable contextual demands [40].…”
Section: Discussionmentioning
confidence: 93%
“…The participants recruited in the current study were adults which may rely on both taxonomic and thematic relations. Third, there has been evidence for the modulation of sentential constraint and L2 proficiency level on L2 word learning ( Pulido, 2003 ; Borovsky et al, 2010 ; Elgort et al, 2015 ; Ma et al, 2015 , 2016 ; Chen et al, 2017 ). Only in highly constraining sentences could the meaning of L2 novel words be derived ( Ma et al, 2015 ), and higher-proficiency L2 learners outperformed than lower-proficiency L2 learners ( Ma et al, 2015 ; Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that L2 contextual word learning is affected by both contextual factors (Elgort & Warren, 2014; Ma et al, 2015; Pulido, 2007; Tekmen & Daloglu, 2006; Vidal, 2011) and lexical factors (e.g. exposure frequency) (Chen et al, 2017; Elgort et al, 2018; Elgort & Warren, 2014; Godfroid et al, 2017; Teng, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As for the contextual factors, studies mainly focused on the contextual constraint of the text and contextual diversity (Brendan et al, 2016; Eva et al, 2017; Manuel et al, 2013). For example, increasing evidence has confirmed that novel words in a high-constraint context are acquired faster and better than those in a low-constraint context (Borovsky et al, 2012; Chen et al, 2017; Frishkoff et al, 2010; Ma et al, 2015, 2016). High-constraint sentences provide more information than low-constraint sentences, and learners could learn more clues about novel words from high-constraint than from low-constraint sentences (Borovsky et al, 2012; Frishkoff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%